One-Step Microfluidic Fabrication of Multi-Responsive Liposomes for Targeted Delivery of Doxorubicin Synergism with Photothermal Effect - Lv S (Dove Medical Press, 2021)
Songwei Lv,1,* Ran Jing,2,* Xiaowu Liu,3,4 Honglei Shi,3,4 Yunfeng Shi,3,4 Xugang Wang,3,4 Xiubo Zhao,1,5 Kai Cao,3,4 Zhong Lv3,4 1School of Pharmacy, Changzhou University, Changzhou, 213164, People’s Republic of China; 2Division of Nephrology, The Affiliated Changzhou NO. 2 People’s Hospital of Nanjing Medical University, Changzhou, 213164, People’s Republic of China; 3Department of Urology, Wujin Hospital Affiliated with Jiangsu University, Changzhou, 213164, People’s Republic of China; 4Department of Urology, The Wujin Clinical College of Xuzhou Medical University, Changzhou, 213164, People’s Republic of China; 5Department of Chemical and Biological Engineering, University of Sheffield, Sheffield, S1 3JD, UK*These authors contributed equally to this workCorrespondence: Kai Cao; Zhong Lv Email caokai9001@126.com; lzabc0105@163.comIntroduction: Cancer of the bladder is one of the most common and life-threatening. Compared with traditional delivery methods, intravesical administration reduces the amount of drugs required, increases the amount of drugs reaching the lesion site, and minimizes systemic exposure to therapeutic agents. To overcome the limitations of urinary voiding, low urothelium permeability, and intermittent catheterization for large dilution and irrigation of drugs in the bladder, magnetic and photothermal-responsive folate receptor-targeted thermal liposomes (FA-TMLs) were designed for the targeted delivery of doxorubicin (DOX) to bladder cancer cells.Methods: Through a microfluidic mixer chip, the magnetic nanoparticles (MNPs), gold nanorods (GNRs) and DOX were encapsulated in folate-modified thermosensitive liposomes to form FA-TMLs@MNPs-GNRs-DOX. DLS, TEM, DSC, and magnetic hysteresis loop were used to characterize the construction of FA-TMLs@MNPs-GNRs-DOX.Results: FA-TMLs@MNPs-GNRs-DOX had a size of about 230 nm and exhibited superparamagnetic properties with the saturation magnetization of 20 emu/g. The DOX loading capacity was as high as 0.57 mg/mL. Additionally, drug release of the FA-TMLs@MNPs-GNRs-DOX could be controlled by temperature change through the photothermal effect. A 980 nm laser beam was selectively irradiated on the FA-TMLs@MNPs-GNRs-DOX to trigger the structural changes of the FA-TMLs, and an average of 95% of the drug was released after 3 hours. The results of cell uptake experiments reveal indicated that FA-TMLs@MNPs-GNRs-DOX were able to specifically bind folate-receptor-positive cells and exhibited toxicity to bladder tumor cells.Conclusion: The present results suggest FA-TMLs@MNPs-GNRs-DOX have a promising multifunctional response and can act as an ideal multifunctional drug delivery system (DDS) for the treatment of bladder tumors.Keywords: bladder cancer, drug delivery, magnetic response, thermo-sensitive liposomes, folate-targeted, photothermal effect